Sexual violence against women in the Western Amazon - Júlia Souza Santos Cargnin; Juliana Scholtão Luna; Débora Melo de Aguiar; Bárbara Teles Cameli Rodrigues; Aldir Alves de Azevedo Filho; Rodrigo Pinheiro Silveira
ABSTRACT OBJECTIVE: To characterize sexual violence cases suffered by women notified by the Sistema de Informação de Agravos de Notificação (Information System for Notifiable Diseases) in the city of Rio Branco (AC - Brazil) from 2011 to 2016. METHODS: Descriptive study based on information from the Notifiable Diseases Information System. The study population consisted on women victims of sexual violence reported in the city of Rio Branco (AC), from 2011 to 2016. RESULTS: The results show a higher number of notifications during 2012, especially among single, brown, and aged between 10 and 14 years victims; usually they have 5 to 8 years of schooling. Normally violence occurred in residences and by a single aggressor, male and non-alcoholic. DISCUSSION: The large number of notifications of pregnant women aged 10 to 14 years corresponds to the compulsory notification of rape of a vulnerable person, identified at the time of prenatal care or childbirth. CONCLUSION: We confirm the susceptibility to sexual violence of young women in Rio Branco, raising the issue of child marriage and teenage pregnancy.